Cytomegalovirus aggravates the autoimmune phenomenon in systemic autoimmune diseases. (July 2018) - Janahi, Essam Mohammed Ahmed; Das, Shukla; Bhattacharya, Sambit Nath; Haque, Shafiul; Akhter, Naseem; Jawed, Arshad; Wahid, Mohd; Mandal, Raju Kumar; Lohani, Mohtashim; Areeshi, Mohammed Yahya; Ramachandran, Vishnampettai G.; Almalki, Shaia; et al.
Abstract: Background: Human Cytomegalovirus (CMV), because of its ability to extensively manipulate host immunity during active infection, has been suggested to be involved in autoimmunity. However, its influence on T-cells and cytokines in systemic autoimmune diseases like systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) is indistinct. Methods: We investigated the in-vitro response of T lymphocytes from SLE and SSc patients to CMV antigen. Functional activity of T lymphocytes was determined by estimating Th1 (IL-2 and IFN-γ) and Th2 (IL-4 and IL-10) cytokines. Results: We observed that CMV antigen stimulation in-vitro resulted in significant increase in CD4:CD8 T-cell ratio in peripheral blood mononuclear cells (PBMCs) from SLE and SSc patients; response dominated by CD4 + than CD8 + memory T-cells. SSc T-cell response was differentiated by aberrant increase in CD4 + CD25 + T-cells. CMV antigen caused elevation in IL-4 and IFN-γ production in both patient PBMCs, whereas IL-2 was also raised in SLE PBMCs. The development of large pool of memory T-cells and overproduction of IFN-γ may result in flare-up of autoimmunity in these patients. Conclusion: Our study provides an insight into the immunopathological potential of CMV-reactive immune cells to develop new potential strategies for targeted therapeutic intervention. Highlights: Elevation in CD4:CD8 T cell ratio in SLE and SSc patient PBMC on CMV stimulation. Aberrant increase in percentages of CD4 + CD25 + T cells differentiates SSc from SLE. IFN-γ overproduction and large memory T cell pool may lead to IL-2 release. Abating naıve T cell pool, particularly of CD4 repertoire, flares up autoimmunity.